2009
DOI: 10.1136/sti.2008.034140
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Neisseria gonorrhoeae and Chlamydia trachomatis in pharyngeal and rectal specimens using the BD Probetec ET system, the Gen-Probe Aptima Combo 2 assay and culture

Abstract: PT and AC2 detected GC and CT with superior sensitivity compared to culture. They detected 73 pharyngeal or rectal GC and CT infections compared to 16 by culture, using a rigorous gold standard. NAATs should be the method of choice for the detection of GC and CT in extragenital sites in men who have sex with men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 28 publications
1
87
0
4
Order By: Relevance
“…18 Nucleic acid amplification tests (NAATs) provide highly sensitive and specific detection of NG and CT in all three susceptible anatomic sites. 19 Nevertheless, no manufacturer currently has a USA Food and Drug Administration approved product for pharyngeal or rectal specimen testing, despite its superiority to culture and recommended use by international guidelines. 6,[19][20][21] Currently in the USA, only laboratories that comply with the Clinical Laboratory Improvement Act and conduct a verification study may use NAATs for non-urethral testing.…”
Section: Traditional Sti Control Methodsmentioning
confidence: 99%
“…18 Nucleic acid amplification tests (NAATs) provide highly sensitive and specific detection of NG and CT in all three susceptible anatomic sites. 19 Nevertheless, no manufacturer currently has a USA Food and Drug Administration approved product for pharyngeal or rectal specimen testing, despite its superiority to culture and recommended use by international guidelines. 6,[19][20][21] Currently in the USA, only laboratories that comply with the Clinical Laboratory Improvement Act and conduct a verification study may use NAATs for non-urethral testing.…”
Section: Traditional Sti Control Methodsmentioning
confidence: 99%
“…NAATs have been shown to be significantly more sensitive than culture in the detection of chlamydia and gonorrhoea, particularly in extra-genital sites (103)(104)(105)(106)(107)(108). Owing to cross-reactivity with nongonorrhoea Neisseria species, all NAAT tests for gonorrhoea from all sites should be confirmed with supplementary tests to improve specificity (109)(110)(111).…”
Section: Chlamydia and Gonorrhoeamentioning
confidence: 99%
“…While there are no NAATs licensed for use with extragenital specimens, several studies have demonstrated that NAATs perform well for the detection of both pharyngeal and rectal C. trachomatis/N. gonorrhoeae infections in MSM (12)(13)(14). Studies evaluating the performance of these testing methodologies have demonstrated sensitivities and specificities exceeding 90% for both organisms from all three sites.…”
mentioning
confidence: 99%